Analysis of The Heavy Metal Content of Zinc (Zn) In Tofu Using Atomic Absorption Spectrophotometer (AAS) - Lutfi, Nadira Nur Hajah; Rizal, Fahmi (Lighthouse Publishing, 2022)
Tofu, which is rich in protein, has long been consumed by the people of Indonesia as a side dish. Tofu is a food made from fermented soybeans and extracts from it. One of the metals that is dangerous and should not be eaten is zinc (Zn). Zinc is a type of heavy metal that is soft and easy to purify. This study aims to determine the content of heavy metal zinc (Zn) contained in tofu by using Atomic Absorption Spectrophotometry (AAS). The advantages of an Atomic Absorption Spectrophotometer (AAS) are specific, low detection limit, from the same solution, several different elements can be measured, can be applied to many types of elements in many types of samples, limit levels that can be determined are very area (mg/L to percent). This research uses a descriptive-analytical method to describe or provide an overview of the object under study through the data. And this research uses the wet destruction method, namely the destruction of the sample with the addition of a solution of nitric acid (HNO3) followed by heating and filtering. The results showed that the concentration of heavy metal Zn in tofu was 0.161 ppm, 0.139 ppm, 0.161 ppm, 0.152 ppm, 0.153 ppm, 0.154 ppm, 0.159 ppm, 0.174 ppm, 0.185 ppm, 0.141 ppm, 0.159 ppm and 0.164 ppm. The conclusion is that the levels of tofu Zn contain zinc metal Zn with levels of 10.3325 mg/kg. The levels of zinc metal Zn are still below the threshold level, so tofu is still safe for consumption.